Seniors and single-use detergent sacs (SUDS): a review of the National Poison Data System from 2012 to 2020. (2nd September 2022) - Aldy, Kim; Du, Tony; Weaver, Mary Madison; Roth, Brett; Cao, Dazhe James
Abstract: Introduction: Exposure to single-use detergent sacs (SUDS), or laundry pods, have declined in the pediatric population between 2015 and 2018. Older adult exposures are less well described, and it is unclear if there is an increased risk of unintentional exposure to SUDS in older adults, especially in those with dementia. This study aims to review SUDS exposures in adults greater than 60-year-old between 2012 and 2020. Methods: Using the National Poison Data System (NPDS), a query was performed for cases involving an acute single substance exposure with substance coded as "laundry detergent unit dose" (Generic code: 0201181, 0201182, and 0201183) in adults greater than 60-years-old between January 1, 2012 and December 31, 2020. Exclusion criteria included unknown age, age less than 60 years, any multi-substance exposure, and chronic or acute-on-chronic acuity. The distribution of cases was analyzed for demographics, exposure circumstances, management, clinical effects, and medical outcome. Results: SUDS exposure reported to NPDS increased from 46 cases in 2012 to 219 cases in 2020. Among the 1289 total reported cases, 94.9% ( n = 1223) were unintentional exposures with an average age of 75-year-old. The majority of exposures occurred in females (69%, n = 883). More than 1 exposure route was reported in 90 cases (7%), and the most common route of exposure was ingestion (64.9%, n = 836). Major effects were identified in 1% ( n = 13) of exposures, and 0.5% ( n = 7) of cases resulted in death. Conclusions: Despite a declining incidence of pediatric SUDS exposure, older adult exposures have increased over 400% between 2012 and 2020.